TRADISI MEWUWUSOI PADA SUKU MORONENE DI KAMPUNG ADAT HUKAEA LAEA KECAMATAN LANTARI JAYA KABUPATEN BOMBANA (1985-2018) - Safitri, Lusiana Dewi; Untarti, Dade Prat (Jurnal Penelitian Pendidikan Sejarah UHO, 2020)
ABSTRACT: This study aims to explain the tradition of mewuwusoi in the Moronene tribe in Hukaea Laea Traditional Village, Lantari Jaya District, Bombana Regency. This study uses historical research methods with the following stages: (1) Heuristics, (2) source criticism, and (3) Historiography which consists of interpretation, explanation, presentation. The results showed that (1) the background of the emergence of the mewuwusoi tradition was that since the Moronene tribe knew the name of agriculture. They do not know for sure because initially the Moronene only knew hunting and gathering because of the development of the times they tried to carry out agriculture. The holding of this tradition is in order to give thanks to God Almighty for their sustenance in agriculture as well as to welcome the coming harvest year. (2) the process of implementing the tradition of mewuwusoi (1985-2018) consists of the stages of preparation, namely the stages of clearing land, Mehedoi / metotamai (self-healing) and Mea'e / meuri (sticky rice from the harvest that is put into the mouths of each group present) and the implementation of the mewuwusoi tradition, among others Mododo (pounding rice), filtering rice after the implementation of Mododo, Molonda (attraction of pounding rice using rhythm), kampiri (place of storing rice, then Lulo Trigger (final harvest party activity) (3) the values contained in the Wuuwusoi tradition, among others, religious values, communicative values and social care values.